2004
DOI: 10.1152/ajpgi.00201.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cortical representation of external anal sphincter contraction: effect of effort

Abstract: The external anal sphincter (EAS) plays a critical role in maintaining fecal continence; however, cerebral cortical control of voluntary EAS contraction is not completely understood. Our aims were to determine the cortical areas associated with voluntary EAS contraction and to determine the effect of two levels of sphincter contraction effort on brain activity. Seventeen asymptomatic adults (ages 21-48, 9 male) were studied using functional magnetic resonance imaging (fMRI) to detect brain activity. Studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 42 publications
3
32
0
1
Order By: Relevance
“…Activation of insula, precuneus, cingulate, sensory/motor, and prefrontal cortices has been reported in relation to swallowing and various other gastrointestinal events, such as subliminal esophageal acid exposure (25), heartburn (22), and external anal sphincter contraction (23). Activation of these same areas by gustatory and olfactory stimuli has also been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Activation of insula, precuneus, cingulate, sensory/motor, and prefrontal cortices has been reported in relation to swallowing and various other gastrointestinal events, such as subliminal esophageal acid exposure (25), heartburn (22), and external anal sphincter contraction (23). Activation of these same areas by gustatory and olfactory stimuli has also been reported.…”
Section: Discussionmentioning
confidence: 96%
“…The posterior cingulate also plays a role in evaluating body orientation in space as well as processing self-relevant emotional and nonemotional information (32). In addition, the posterior cingulate is activated during volitional external anal sphincter contraction (9). The insula, with its many interconnections with limbic and other paralimbic structures as well as sensory association areas, has been implicated as an integrative element in sensory and motor function (1).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have dealt with transcranial magnetic or electrical stimulation of the motor cortex, which could trigger contractions of the external sphincter and the pelvic floor 35 -38 . Only Kern et al 39 have described the cortical activation pattern of voluntary anal sphincter contraction in a recently published fMRI study. Their findings, in keeping with the present study, showed that repeated contraction of the external anal sphincter produced activation of the motor as well as the supplementary motor cortex and, in addition, activation of the primary and secondary somatosensory cortex and the insula.…”
Section: Cortical Activity With Pelvic Floor Activationmentioning
confidence: 99%
“…Activation of centres other than the primary motor cortex was attributed to the necessary design and control of sphincter contraction 39 . However, of particular interest is the intense activation of the insula in the present study and in that by Kern et al 39 , since the role of the insula in voluntary motor activity still remains unclear. Interestingly, Kern et al 39 observed more intense activation of the insula in females.…”
Section: Cortical Activity With Pelvic Floor Activationmentioning
confidence: 99%